PARP2 downregulation in T cells ameliorates lipopolysaccharide-induced inflammation of the large intestine - Bencsics, Máté; Bányai, Bálint; Ke, Haoran; Csépányi-Kömi, Roland; Sasvári, Péter; Dantzer, Françoise; Hanini, Najat; Benkő, Rita; Horváth, Eszter M. (Frontiers in Immunology, 2023)
Introduction T cell-dependent inflammatory response with the upregulation of helper 17 T cells (Th17) and the downregulation of regulatory T cells (Treg) accompanied by the increased production of tumor necrosis alpha (TNFa) is characteristic of inflammatory bowel diseases (IBD). Modulation of T cell response may alleviate the inflammation thus reduce intestinal damage. Poly(ADP-ribose) polymerase-2 (PARP2) plays role in the development, differentiation and reactivity of T cell subpopulations. Our aim was to investigate the potential beneficial effect of T cell-specific PARP2 downregulation in the lipopolysaccharide (LPS) induced inflammatory response of the cecum and the colon. Methods Low-dose LPS was injected intraperitoneally to induce local inflammatory response, characterized by increased TNFa production, in control (CD4Cre; PARP2+/+) and T cell-specific conditional PARP2 knockout (CD4Cre; PARP2f/f) mice. TNFa, IL-1b, IL-17 levels were measured by ELISA, oxidative–nitrative stress was estimated by immunohistochemistry, while PARP1 activity, p38 MAPK and ERK phosphorylation, and NF-kB expression in large intestine tissue samples were examined by Western-blot. Systemic & local T cell subpopulation; Th17 and Treg alterations were also investigated using flowcytometry and immunohistochemistry. Results In control animals, LPS induced intestinal inflammation with increased TNFa production, while no significant elevation of TNFa production was observed in T cell-specific PARP2 knockout animals. The absence of LPS-induced elevation in TNFa levels was accompanied by the absence of IL-1b elevation and the suppression of IL-17 production, showing markedly reduced inflammatory response. The increase in oxidative-nitrative stress and PARP1-activation was also absent in these tissues together with altered ERK and NF-kB activation. An increase in the number of the anti-inflammatory Treg cells in the intestinal mucosa was observed in these animals, together with the reduction of Treg count in the peripheral circulation. Discussion Our results confirmed that T cell-specific PARP2 downregulation ameliorated LPS-induced colitis. The dampened TNFa production, decreased IL-17 production and the increased intestinal regulatory T cell number after LPS treatment may be also beneficial during inflammatory processes seen in IBD. By reducing oxidative-nitrative stress and PARP1 activation, T cell-specific PARP2 downregulation may also alleviate intestinal tissue damage.